A case of spontaneous pyeloduodenal fistula - Hamamoto, Y (Hinyokika kiyo. Acta urologica Japonica, 1999)
A 61-year-old woman visited our hospital complaining of right flank pain and fever. The radiograph demonstrated multiple renal calculi. Radio renography showed no uptake in the right kidney. Therefore, we diagnosed her with pyonephrosis, and recommended open nephrectomy. However, she selected the conservative treatment with extra corporeal shockwave lithotripsy (ESWL). In spite of disappearance of multiple calculi, pyuria continued for 3 months after ESWL. Retrograde pyelography showed a fistula from the right pelvis into the duodenum. The patient was successfully treated by nephrectomy and duodeno-fistelectomy